Trust or distrust An indigenous study on the perspective of undergraduate students towards Malaysian politicians - Seow Ling, Ooh; Bee Seok, Chua; Uichol Kim (ResearchGate, 2013)
Trust in politicians plays a very important role to strengthen a relationship between the people and politician is especially in democractic countries (Marien & Hooghe, 2011). Research showed that the levels of trust in politicians have been declining in recent years (Keele, 2007). However, study on the levels and the reasons of trust politician are still underexplored especially in Asian country. Hence, the purpose of this study is to figure out the frequency of trust in politicians in Malaysia and to identify peoples’ beliefs and views (stereotype) against their politicians in the indigenous context. This study was conducted using a qualitative approach involving a total of 858 undergraduate students. The results obtained from the open-ended questions showed that only 24% declared themselves as trusting the politicians. They trusted the politicians mostly because of the role of politicians (63.5%) and politicians’ characteristic (36.5%), while 76% reported they distrust politicians. Distrust towards politicians revealed four main categories which are politicians’ characteristic (48%), political motive (23%), verbal (22%) and the role of politicians (7%). The issue of trust towards politicians in the local context will be discussed.